Zinc and pH modulate the ability of insulin to inhibit aggregation of islet amyloid polypeptide - Samuel D. McCalpin; Lucie Khemtemourian; Saba Suladze; Magdalena I. Ivanova; Bernd Reif; Ayyalusamy Ramamoorthy (Communications Biology, 2024)
Abstract Aggregation of the human islet amyloid polypeptide (hIAPP) contributes to the development and progression of Type 2 Diabetes (T2D). hIAPP aggregates within a few hours at few micromolar concentration in vitro but exists at millimolar concentrations in vivo. Natively occurring inhibitors of hIAPP aggregation might therefore provide a model for drug design against amyloid formation associated with T2D. Here, we describe the combined ability of low pH, zinc, and insulin to inhibit hIAPP fibrillation. Insulin dose-dependently slows hIAPP aggregation near neutral pH but had less effect on the aggregation kinetics at acidic pH. We determine that insulin alters hIAPP aggregation in two manners. First, insulin diverts the aggregation pathway to large nonfibrillar aggregates with ThT-positive molecular structure, rather than to amyloid fibrils. Second, soluble insulin suppresses hIAPP dimer formation, which is an important early aggregation event. Further, we observe that zinc significantly modulates the inhibition of hIAPP aggregation by insulin. We hypothesize that this effect arose from controlling the oligomeric state of insulin and show that hIAPP interacts more strongly with monomeric than oligomeric insulin.